Penentuan Jadwal dan Rute Perjalanan Kapal dengan Batasan Waktu dan Jumlah Kunjungan - I Gede Agus Widyadana; Richard Wibisono (Institute of Research and Community Outreach - Petra Christian University, 2016)
Scheduling and routing are important for a shipping company. In this paper a scheduling and routing model is developed to solve a shipping company problem. The model is different to some previous models since it considers the company’s constraints such as number of ports that can be visited in one route, number of calls in each port and minimum gap between consecutive visits. The model is applied in one shipping company in Surabaya, Indonesia and is solved using insertion heuristic and simulated annealing. The result shows that simulated annealing method can reduce 18.2% of total distance compare to previous company’s schedule and routes.